Unsung heroines : single mothers and the American dream - Sidel, Ruth (University of California Press, 2006)
Gives political-economic analysis that provides historical background on the way American social policy has evolved and compares the situation in the US to the social policies and ideologies of other countries. This book introduces courageous population of women committed to their families, holding fast to quintessential American values.